Exploring teacher effects on intensifying and minimizing mathematics anxiety among students in Sokoto State, Nigeria - Norulhuda Ismail; Aliyu Garba; Sharifah Osman; Nor Hasniza Ibrahim; Muhammad Abd Hadi Bunyamin (Institute of Advanced Engineering and Science, 2022)
Mathematics anxiety is the feeling of tension and fear which interferes with the manipulation of numbers in ordinary life and academic setting. This study aimed at exploring students’ level of mathematics anxiety and teacher behavior and speech which intensifies and minimizes mathematics anxiety among secondary schools in Sokoto state, Nigeria. In total, 109 questionnaires regarding mathematics anxiety named the cognitive, emotion, physical-mathematics anxiety rating (CEP-MAR) were distributed to students and 102 were returned. From the responses in the questionnaire, 20 of the most mathematics anxious individuals were selected to participate in a photovoice project. These 20 students were given cameras and asked to capture classroom events, which impact on their mathematics anxiety. Afterwards, a one-to-one semi-structured interview was conducted with each student to discuss the photos. The findings disclosed that teachers’ behavior and speech such as being too quick in mathematics classroom lessons, giving too many notes, exercises, punishments and embarrassing/alarming statements have a significant effect in intensifying mathematics anxiety. The findings also showcased that quiz/competitions, good learning environment, intrinsic and extrinsic motivational statements help in minimizing mathematics anxiety. This study provides further evidence that teachers have both positive and negative effect on students’ mathematics anxiety.